Interaction between emotion lability, emotion regulation and structural brain abnormalities in patients with anorexia nervosa and borderline personality disorder - Wayda-Zalewska, Magdalena; Pluta, Agnieszka; Wolak, Tomasz; Wojtczak, Mateusz; Wojciechowski, Jakub; Kucharska, Katarzyna (Frontiers in Neuroscience, 2025)
ObjectiveEmotion dysregulation is a significant challenge in borderline personality disorder (BPD) and anorexia nervosa (AN). These disorders often exhibit maladaptive emotion regulation (ER) strategies, which can vary widely. This study aimed to assess cortical thickness and volume, and their relationship with emotional lability and regulation in females with AN and BPD.MethodsThe study involved 32 subjects with AN, 46 with BPD, and 41 age-matched healthy controls (HC). Participants underwent brain magnetic resonance imaging utilizing structural magnetic resonance imaging (MRI) alongside validated psychological assessment tools to measure emotional lability and regulation. Volumetric and cortical thickness measurements were assessed, and semi-partial Pearson’s correlations were used to analyze associations with psychological subscales.ResultsSubjects with AN demonstrated higher level of adaptive strategies and lower maladaptive strategies compared to those with BPD, except in self-blame, which showed no difference between clinical groups. The results suggest that BPD patients demonstrate significantly higher emotional lability and reliance on maladaptive regulation strategies. Neuroimaging data revealed significant structural differences between HC and the clinical groups, particularly in the prefrontal cortex, nucleus accumbens, hippocampus, and insula. Few significant correlations were also observed between variables associated with emotion dysregulation/lability and gray matter volume/thickness in the frontal regions, cingulate cortex, insula, and basal nuclei.ConclusionThe clinical groups differed from each other and from the group of HC in terms of the variables studied. The study highlights the critical role of neurobiological mechanisms in informing the development of targeted therapeutic interventions for emotion dysregulation.